Compact Growth Habit Tomatoes - Monica Ozores-Hampton; Aline Coelho Frasca; John Scott; Samuel Hutton (EDIS)
Alternatives to the traditional production system that reduce production cost would be economically beneficial to the Florida tomato industry. Compact growth habit tomatoes are determinate varieties with a unique architecture that may provide the basis for a viable alternative production system for Florida. These tomatoes have low growth and spreading characteristics, forming compact plants that hold fruit above the ground on short branches. They do not require staking, tying, or pruning, so they may be used by the Florida mature-green fresh-market tomato growers to reduce labor costs. This 5-page fact sheet was written by Monica Ozores-Hampton, Aline Coelho Frasca, John Scott, and Samuel Hutton, and published by the UF Department of Horticultural Sciences, September 2013.